Contribución al desarrollo de un sistema de tomografía microondas : nivel sistema (2017)
"This document presents the 'Contribution to the development of a system of microwave tomography: high level'. Initially, the objectives are set to achieve a high level design for a microwave tomography (MWT) system, limiting the scope of the project into a high level design." -- Tomado del Formato de Documento de Grado.